In vivo modulation of nonphotochemical exciton quenching (NPQ) by regulation of the chloroplast ATP synthase - Kanazawa, Atsuko (The National Academy of Sciences, 2002)
Nonphotochemical quenching (NPQ) of excitation energy, which protects higher plant photosynthetic machinery from photodamage, is triggered by acidification of the thylakoid lumen as a result of light-induced proton pumping, which also drives the synthesis of ATP. It is clear that the sensitivity of NPQ is modulated in response to changing physiological conditions, but the mechanism for this modulation has remained unclear. Evidence is presented that, in intact tobacco or Arabidopsis leaves, NPQ modulation in response to changing CO(2) levels occurs predominantly by alterations in the conductivity of the CF(O)-CF(1) ATP synthase to protons (g [Formula: see text]). At a given proton flux, decreasing g [Formula: see text] will increase transthylakoid proton motive force (pmf), thus lowering lumen pH and contributing to the activation of NPQ. It was found that an ≈5-fold decrease in g [Formula: see text] could account for the majority of NPQ modulation as atmospheric CO(2) was decreased from 2,000 ppm to 0 ppm. Data are presented that g [Formula: see text] is kinetically controlled, rather than imposed thermodynamically by buildup of ΔG(ATP). Further results suggest that the redox state of the ATP synthase γ-subunit thiols is not responsible for altering g [Formula: see text]. A working model is proposed wherein g [Formula: see text] is modulated by stromal metabolite levels, possibly by inorganic phosphate.